Prevalencia y factores asociados a somnolencia diurna excesiva en población adulta del norte del Perú - Flores, Lina (2025)
Objective: To determine the prevalence and factors associated with excessive daytime sleepiness (EDS) in an adult population between 30 and 69 years of age in Tumbes, Peru. Material and Methods: Cross-sectional analysis of secondary data from a population-based study conducted between 2016 and 2017 (pre-pandemic). EDS was evaluated using the Sleepiness Epworth Scale (modified Peruvian version). Potential associated factors were demographic and behavioral variables, as well as obesity and mental health indicators. Associations of interest were evaluated using crude and adjusted Poisson regression models, and prevalence ratios (PR) and 95% confidence intervals (95% CI) were reported. Results: Data from 1,609 adults was included. Their mean age was 48.2 years (SD: 10.6), 810 (50.3%) were women, and 105 (6.5%; 95% CI: 5.4% - 7.8%) had EDS. In the multivariable model, EDS was more frequent in women (PR: 1.78; 95% CI: 1.11–2.85), among those aged 50–59 years (PR:1.94; 95% CI 1.09–3.48), those currently working (PR: 2.54; 95% CI: 1.62–3.97), those with obesity (PR: 2.19; 95% CI: 1.27–3.76), and those with depressive symptoms (PR: 3.08; 95% CI: 1.97–4.80). Higher education was inversely associated with EDS (PR: 0.47; 95% CI: 0.23–0.96). Conclusions: The pre-pandemic prevalence of EDS was 6.5%. Women, some age groups, being employed, being obese, and having depressive symptoms showed a positive association with the presence of EDS, whereas only higher education showed a negative association.